Accelerated weathering analysis of jute reinforced cashewnut shell liquid modified soy based green composite. (4th November 2020) - Avancha, Sridevi; Behera, Ajaya Kumar; Sen, Ramkrishna; Adhikari, Basudam
Abstract: Cashew nut shell liquid (CNSL) is improved as a soy resin system when aldehyde‐based curing agent is used for crosslinking. In this work, composites were prepared by reinforcing sodium hydroxide treated jute felts with CNSL modified soy resin and characterized in terms of water resistance, mechanical properties, dynamic mechanical properties and screw drilling properties. Addition of 4 wt% CNSL in soy resin increased water resistance of the composite by 10% whereas tensile properties of composite improved by about 40%. Maximum storage modulus of CNSL based composite was found 8412 MPa as compared to 1092 MPa of jute‐soy composite without CNSL. Composites were exposed to accelerated weather and checked for dimensional stability, change in weight and mechanical properties. These composites could find wide applications in railway and automobile interiors, furniture, toysand so forth. Abstract :